PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TWO TAY TWO TRAY UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 9 PANGKALAN SIRIH KECAMATAN RUPAT - Rita Rita; Otang Kurniaman; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This education is implemented because of the low of IPS study result of fourth graders of SD Negeri 9 Pangkalan Nyirih, KKM set at school that is 65. Of the 20 students who reach KKM 10 students while students who do not reach KKM as many as 10 students with the average value of students (50%). To overcome the problem, the researcher applied the learning model of TSTS, the purpose of this research is to improve the learning result of IPS students of Elementary School 9 IV Pangkalan Nyirih Rupat District with the application of TSTS learning model, the research result obtained the average score of the basic score of average ability of students 50 increases in the first cycle of 60 on the second cycle also increased by an average of 80. Activity of teachers at the first meeting of the cycle I percentage was 71.28% with good category and at the second meeting the same cycle percentage is 78.57% with Perentae Very Good and on activity teachers cycle II first meeting of the 82.14% of the percentage with very good category and at the second meeting increased to 85.71% with Excellent category. The activity of the students at the first cycle meeting was 62.5% with sufficient category, at the second meeting of cycle I the percentage was 70.83% with good category, in the first meeting of the second cycle the percentage was 83.33% with very good category, at the second meeting increased to 87.5% with a very good category of this study can be concluded that by applying the model of learning TSTS can improve learning outcomes IPS fourth grade students SD Negeri 9 Pangkalan Nirih.Keywords: learning model of TSTS, learning result of IPS